Comparison of Humpty Dumpty and BUCH Scales for Assessment of Fall Risk Among Pediatric Patients - GÜRKAN, AYSEL (DR BEHCET UZ COCUK HASTALIKLARI VE CERRAHISI, 2019)
Objective: The aim of this study is to determine the predictive validity of the Humpty Dumpty and OUCH scales in the assessment of the fall risk of child patients. Methods: This methodological study was carried out between October 2016 and April 2017 in all the inpatient wards of a child hospital in Ankara except for its intensive care unit and emergency services. Its sampling consisted of children aged 0-18 receiving inpatient treatment. The data of 200 patients who met the inclusion criteria and had not a fall incident was obtained prospectively between October 2016 and April 2017 and the data of 16 patients who had a history of fall incident between 2014 and 2015 were obtained retrospectively. The data were collected through the BUCH and Humpty Dumpty fall risk assessment scales. The predictive validity of both scales was assessed based on sensitivity, specificity, positive predictive value, negative predictive value, and the area values under ROC curve. Results: The sensitivity, specificity, and positive and negative predictive values were found to be 87.5%, 60%, 14.8%, and 98.3% (with a cut-off point of 13.5%), respectively, for the Humpty Dumpty scale and 100%, 33.5%, 10.7%, and 100% (with a cutoff point of 15.5%) and 87.5%, 41.0%, 10.6%, and 97.6% (with a cut-off point of 16.5%), respectively, for the BUCH scale. The area under ROC curve was detected to be 0.739 for Humpty Dumpty and 0.657 for WO scales. Conclusion: The Humpty Dumpty scale offered better predictive values relative to BUCH scale in the assessment of fall risk of child patients.
Keywords: Pediatric patient; fall; risk identification; predictive validity; PREVENTION